Simple bioconjugate chemistry serves great clinical advances: albumin as a versatile platform for diagnosis and precision therapy - Liu, Zhibo; Chen, Xiaoyuan (Chemical Society reviews, 2016)
Albumin is the most abundant circulating protein in plasma and has recently emerged as a versatile protein carrier for drug targeting and for improving the pharmacokinetic profile of peptide or protein based drugs. Three drug delivery technologies related to albumin have been developed, which include the coupling of low-molecular weight drugs to exogenous or endogenous albumin, conjugating bioactive proteins by albumin fusion technology (AFT), and encapsulation of drugs into albumin nanoparticles. This review article starts with a brief introduction of human serum albumin (HSA), and then summarizes the mainstream chemical strategies of developing HSA binding molecules for coupling with drug molecules. Moreover, we also concisely condense the recent progress of the most important clinical applications of HSA-binding platforms, and specify the current challenges that need to be met for a bright future of HSA-binding. Albumin is the most abundant circulating protein in plasma and has recently emerged as a versatile protein carrier for drug targeting and for improving the pharmacokinetic profile of peptide or protein based drugs.